Changes in the Superior Vena Cava Area During Inspiration and Expiration in Relation to Emphysema. (14th April 2015) - Matsuoka, Shin; Yamashiro, Tsuneo; Kotoku, Akiyuki; Matsushita, Shoichiro; Fujikawa, Atsuko; Yagihashi, Kunihiro; Kurihara, Yasuyuki; Nakajima, Yasuo
Abstract Background: In patients with emphysema, increased intrathoracic pressure is closely related to hyperinflation and leads to hemodynamic impairments. Both intrathoracic pressure and hemodynamics such as venous return are affected by the respiratory phase. Therefore, respiratory variations in hemodynamics may be associated with the extent of emphysema that causes increased intrathoracic pressure. The current study was designed to evaluate the relationship between respiratory phasic variations in the area of the superior vena cava (SVC) and the extent of emphysema. Methods: We measured the SVC area and calculated the ratio of the SVC area in inspiratory and expiratory scans (i/e-SVC ratio) in 101 patients with emphysema who underwent both inspiratory and expiratory CT. The correlation of the i/e-SVC ratio with the extent of emphysema (%LAA) obtained by CT images was evaluated. Multiple linear regression analysis using i/e-SVC ratio as the dependent variable was performed. Results: The i/e-SVC ratio had a significant positive correlation with%LAA (ρ = 0.582, p <0.0001). The i/e-SVC ratio was significantly higher in patients with severe emphysema (0.86 ± 0.13) than in patients with mild-moderate emphysema (0.69 ± 0.13) (p <0.0001). Multiple linear regression analysis showed that%LAA was the only independent predictors of the i/e-SVC ratio (r2 = 0.471, p = 0.0006). Conclusion: Respiratory phasic variations in the SVC area are significantly correlated with the extent of emphysema.